LEGAL PROTECTION FOR CONSUMERS IN EQUITY-BASED CROWDFUNDING ACTIVITIES IN INDONESIA - Afinawifi; Dian Purnama Anugerah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Financial Technology has developed very rapidly in recent years. Among the products of its creation is crowdfunding. Crowdfunding itself is defined as the practice of funding a project or business by collecting small amounts of money from large numbers of people, and usually via the internet. One form of crowdfunding that is currently in demand in several parts of the world is Equity-based Crowdfunding. Equity-based crowdfunding is a funding transaction in which a fundraising company offers a share of shares in the company as compensation for the investment made through the platform, namely the website. There is no regulation on this activity in Indonesia. However, if the future constitution regarding this matter will be made, one thing that should be emphasized will be consumer protection. Regulators, in this case, must provide protection by considering the nature and purpose of crowdfunding itself to make it easier for new companies to raise funds without going through a mechanism that consumes a high value at a fairly long process.